Guernsey : Financial Sector Assessment Program Update-Detailed Assessment of Observance on Insurance Core Principles. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Guernsey's status as the largest international insurance center in Europe hinges on its progressive infrastructure and operational flexibility. Guernsey updates its regulatory regime continually and has implemented all the recommendations arising from the 2003 Offshore Financial Center (OFC) assessment. The updated regulatory framework has a high level of observance with the Insurance Core Principles (ICPs). The Guernsey Financial Services Commission (GFSC) should expand its range of enforcement powers and also implement the public disclosure standards established by the International Association of Insurance Supervisors (IAIS). The mission advised the GFSC to continually assess the practical implementation of Own Solvency Capital Assessment (OSCA).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet